PENGARUH PENDIDIKAN KESEHATAN TERHADAP PERAN ORANG TUA DALAM MENJAGA KESEHATAN GIGI DAN MULUT SISWA KELAS I DI SDN KAKATUA MAKASSAR - Alimuddin, Hadijah; Aminawati, Aminawati; Ramadhani, Aqilah; Rahmadani, Nanang; Nurhaedah, Nurhaedah; Sangkala, Sangkala (Jurnal Ilmiah Amanah Akademika, 2021)
One of the causes of dental and mouth problems in the society is the behavioral factor or attitude to ignore the dental and mouth hygiene. This is based on the lack of knowledge of the importance of dental and mouth care. This study aims to determine the effect of providing dental and mouth care. This type of research is a quasi-experimental with One Group pretest-posttest design. The population in this study were the parents of grade 1 students with a total of 44 people. Determination of the sample using total sampling. The data was collected use the questionare that spread through applications online social to respondents and statistically analyzed by using the univariate and bivariate test (t- test). Based on the results of this study, the role of the parent from 1st grade students in SDN Kakatua Makassar before being given health education in the initial conditions (pre-test), obtained an average value of the role of parents 23,48 (SD =2,162), and after the implementation of the provision of health education obtained an average value of 26,14 (SD = 1,863). With p value 0,000<0,05. This means that there is an effect of health education on the role of parents in maintaining oral health for grade 1 students at SDN Kakatua Makassar in 2021. Counseling on maintaining children's dental and oral health can be recommended as an alternative action to assist parents in maintaining their child's dental and oral health.